2014
DOI: 10.1111/j.2040-0209.2014.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Political Economy of Climate Compatible Development: Artisanal Fisheries and Climate Change in Ghana

Abstract: SummaryInterest in prospects for policy processes that contribute to development, climate change adaptation and mitigation, known as 'climate compatible development', has been growing in response to increasing awareness of the impacts of climate change. This paper provides insight into the complex political economy of climate compatible development in Ghana's artisanal fisheries, a sector that has received comparatively little attention in climate change literature and policy processes. It focuses on two conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…This has been exacerbated by the limited control over fishing effort and a lack of regular monitoring, which is characteristic of most artisanal fisheries, and which often leads to a rapid growth in artisanal fisheries under open access regimes (Mathew, 2003;Tanner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This has been exacerbated by the limited control over fishing effort and a lack of regular monitoring, which is characteristic of most artisanal fisheries, and which often leads to a rapid growth in artisanal fisheries under open access regimes (Mathew, 2003;Tanner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This approach could be less effective but lead to better cooperation (Keohane & Victor, ). A bottom‐up approach also allows for more regionalization of the global response, as argued by various studies of specific countries or regions (Chaudhary, Narain, Krishna, & Sagar, ; Francesch‐Huidobro, ; Jones & Carabine, ; Käkönen, Lebel, Karhunmaa, Dany, & Try, ; Kim, ; López‐Vallejo, ; Nagoda, ; Tanner, Mensah, Lawson, Gordon, Godfrey‐Wood, & Cannon, ; Waterbury, ).…”
Section: Political Economy Of Responses To Climate Changementioning
confidence: 99%
“…Stakeholders' respective agendas will naturally be influenced by these processes. It has been shown that political-economic factors have profound impacts for the achievement of development, mitigation and adaptation [13]. Likewise, CCD goals are routinely influenced and shaped by socio-ecological environments [98].…”
Section: A Framework For Evaluating the Social Justice Implications Omentioning
confidence: 99%